2018
DOI: 10.1017/s0007114518002507
|View full text |Cite
|
Sign up to set email alerts
|

Lysozyme-rich milk mitigates effects of malnutrition in a pig model of malnutrition and infection

Abstract: Malnutrition remains a leading contributor to the morbidity and mortality of children under the age of 5 years and can weaken the immune system and increase the severity of concurrent infections. Livestock milk with the protective properties of human milk is a potential therapeutic to modulate intestinal microbiota and improve outcomes. The aim of this study was to develop an infection model of childhood malnutrition in the pig to investigate the clinical, intestinal and microbiota changes associated with maln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 48 publications
3
18
0
Order By: Relevance
“…Animals in this model consistently present with severe wasting; significant intestinal changes including decreased crypt depth, decreased thickness of the lamina propria, increased transcellular and paracellular permeability, and decreased weight and length of small intestine [23 , 24] . One notable discrepancy was that the malnourished piglets in this model did not exhibit hypoalbuminemia [23 , 24] , which is typically observed in children with SAM [13] .…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Animals in this model consistently present with severe wasting; significant intestinal changes including decreased crypt depth, decreased thickness of the lamina propria, increased transcellular and paracellular permeability, and decreased weight and length of small intestine [23 , 24] . One notable discrepancy was that the malnourished piglets in this model did not exhibit hypoalbuminemia [23 , 24] , which is typically observed in children with SAM [13] .…”
Section: Introductionmentioning
confidence: 91%
“…Carbohydrates, amino acids, and lipids are digested and metabolized similarly in pigs and humans and the digestion products have similar effects on gastrointestinal development [21] . Several piglet models of SAM have been developed over the last decade [23] , [24] , [25] , [26] - 27] . Garas et al [23] developed, and subsequently replicated [24] , a model of SAM rooted in protein-energy malnutrition, in which severely malnourished piglets exhibited several clinical signs of SAM observed in humans, including alterations in intestinal morphology and function, hematology, and serum biochemistry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that under a calorie restricted state the passage of small ions is altered, but not the integrity of tight junctions. In contrast, protein-energy malnourishment in pigs (50% caloric restriction and protein deficient diet), did result in greater FD4 permeability [52,53]. These inconsistencies may be due to the specific nature of the malnutrition model.…”
Section: Discussionmentioning
confidence: 94%
“…These inconsistencies may be due to the specific nature of the malnutrition model. In studies where macromolecule permeability was increased [52,53], pigs were both energy restricted and fed protein deficient diets, whereas in studies where no change in macromolecule permeability was observed [51; the current study], pigs were energy restricted but fed diets that met their specific nutrient requirements and should not have been in a caloric deficit severe enough to become deficient in specific nutrients such as protein, which is used preferentially and disproportionately by the intestine for maintenance [54]. In support of this, we observed no difference in the phosphorylation (activation) of the energy sensing protein AMPK in the jejunum.…”
Section: Discussionmentioning
confidence: 99%